2018
DOI: 10.1177/1475090218813731
|View full text |Cite
|
Sign up to set email alerts
|

Cradle-to-gate life cycle assessment of ships: A case study of Panamax bulk carrier

Abstract: Seaborne transport plays an important role in global transportation, and ships' emissions are worth considering. By applying life cycle assessment method, the environmental impacts of ships could be evaluated. Life cycle assessment is an effective tool as this method provides a holistic perspective of a product or a service in its life cycle. In an attempt to clarify emissions released from the cradle-to-gate life cycle of ships, especially from processes in shipbuilding which were not considered adequately fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Two studies closer to the subject of this report is a LCA of an LNG-fuelled ship within the South Korean domestic trade by Jeong et al (2019) and a partial LCA of a Panamax bulk carrier by Tuan and Wei (2019). According to the study by Jeong et al (2019), emissions for using LNG as a fuel are substantially lower than sailing on MGO.…”
Section: Lca Research In Marine Industrymentioning
confidence: 81%
See 2 more Smart Citations
“…Two studies closer to the subject of this report is a LCA of an LNG-fuelled ship within the South Korean domestic trade by Jeong et al (2019) and a partial LCA of a Panamax bulk carrier by Tuan and Wei (2019). According to the study by Jeong et al (2019), emissions for using LNG as a fuel are substantially lower than sailing on MGO.…”
Section: Lca Research In Marine Industrymentioning
confidence: 81%
“…Jeong et al (2019) concludes that LCA of marine fuels is a beneficial option for a comprehensive overview of emissions levels, and a viable complement in areas where current marine emission indicators are lacking. Tuan and Wei's (2019) LCA of the bulk carrier covers the stages from material extraction until shipbuilding and sea trials. Comparable to the offshore wind power system studies, Tuan and Wei (2019) reports that the majority of environmental effects are derived from material extraction and the production phase.…”
Section: Lca Research In Marine Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Hua et al (2019) revealed that varied operation conditions of engines played an important role in quantifying pollutants. Tuan and Wei (2019) examined emissions from detailed shipbuilding processes upon which similar studies had not touched.…”
Section: Past Researchmentioning
confidence: 99%
“…Therefore, this study is carried out to provide a detailed example for LCA practitioners, which is in accordance with ISO 14040. In order to continue the study on cradle-to-gate LCA carried out by the authors in Tuan and Wei, 45 this study aims to apply the cradleto-grave LCA method to evaluate the environmental impacts of an oil tanker in its entire life cycle. Some typical applications of LCA method in the shipbuilding and shipping sectors are also briefly reviewed.…”
Section: Introductionmentioning
confidence: 99%